Methodological overcoming strategy for basketball coaches in the teaching of tactics - José Benigno Díaz-Campello; Hirbins Manuel Dopico-Pérez (Universidad de Guantánamo, 2019)
The objective of the present research is to develop a methodological overcoming strategy for basketball coaches in the teaching of tactics. Theme of vital importance and relevance to the challenges of modern sport. For the realization of the research a sample of 24 coaches with an average of 14 years in their work as basketball coaches is taken. A systematization of the theoretical foundations that sustain the tactical preparation in basketball is carried out and the strategy is elaborated, which will allow raising the preparation of these professionals, contributing to the acquisition of pedagogical-professional skills.